Performance and Analysis of Multi-Level Inverters Integrated to Induction Motor with V/f Principle Speed Control - et. al., Deepak Kumar Jha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper three different levels, 3ph multilevel inverters are integrated to Induction Motor (IM) using V/f principle for speed control of the motor. The multilevel inverter used is diode clamped inverter, considering 7-level 9-level and 11-level for the analysis. The V/f control system is further updated with fuzzy logic interface system replacing the closed loop conventional PI controller. The efficiency of the induction motor is studied with different multilevel inverters using PI and fuzzy controllers. The design and analysis are carried out in MATLAB Simulink GUI environment and graphs are represented with respect to time